Design and engineer a domestic use vertical farm unit for growing green vegetables and herbs - Yee, Barry Kar Kit (2017)
Food security in Singapore is among some of the highest in the world but are volatile due to geopolitics nature within Southeast Asia. With 90% of Singapore’s food being imported, occurrence of undesirable geopolitical playout could put the densely populated red nation into state of famine. This report aims to seek solution for improving food independence through means of vertical farming that is both efficient and sustainable. With well-established vertical farming businesses, the focus have been shifted to domestic market which aims to achieve significant improvement in food independence. Study was done to conclude the best type and species of crop that grows under terms of predetermined conditions and type of hydroculture suitable for targeted domestic market, where factors such as maintenance and operating cost would pose as a deterrence factor to potential users. As domestic product, it was a design challenge to make the system a practical vegetative infrastructure while inciting aesthetic sense of the natural environment. The disparity in required sunlight exposure between crops brings about another engineering challenge, making even sunlight distribution across yield evidently critical especially when user plans to yield diversify crops. As such, the solution proposed in this reports is a sustainable, easily maintained, low power consumption, self-propelled vertical farming system with variable rotational speed to solve the problem. Unlike large scale vertical farms that dwells on city farming with centralized operations that yielding high quantity in short period, the established solution seeks food independence through high unit volume in the potential decentralized domestic market.